Aplicação do Modelo Transteórico para consumo de óleos e gorduras e sua relação com consumo alimentar e estado nutricional em um Serviço de Promoção da Saúde - Renata Andrade de Medeiros Moreira (2010)
The Transtheoretical Model is to aim facilitate behaviors of change such asexcessive consumption of oils and fats, by the stages. This study aimed toevaluate the application of the Transtheoretical Model for oils and fats and itsrelation to food consumption and nutritional status the Public Health Serviceusers of Belo Horizonte, Minas Gerais. The sample consisted of individualsaged 18 years or more who entered Academia da Cidade at East SanitaryDistrict from October 2007 to November 2008. Data collection includedimplementation of algorithm for oils and fats, application of three 24-hour recallto reclassificate the users how that consumption of lipids and anthropometricmeasurements (weight, height, waist circumference, waist-hip ratio and bodymass index). Statistical analysis was descriptive and analytic, and included thechi-square test, Fisher exact, Mann-Whitney, ANOVA, Tukey HSD, Kruskal-Wallis and McNemar test (p<0.05). Of the 145 respondents, 91.0% werewomen aged 53.4 ± 12.3 years. It was found that in the algorithm classification,2.8% were in pre-contemplation, 9.0% in contemplation, 11.7% decision, 20.7%action and 55.9% in maintenance. Already after reclassification, 5.5% were inpre-contemplation, 20.0% contemplation, 24.1% decision, 29.0% action and21.4% in maintenance. There was significant difference in the stages beforeand after reclassification (p<0.001), denoting the importance of this study. Therelation of stages of change and nutritional status were not significant difference(p>0.05), but the stages were associated with intake of foods rich in fats;consumption of fat, that show validation of the instrument, saturated fatty acidsand monounsaturated fat, and cholesterol (p<0.05). It follows that the algorithmafter validation of the user perception of oils and fats consumption is animportant tool for evaluating the feeding behavior to be used as an aid to foodand nutrition education aimed at more effective interventions.